A3_6 To Power a Miracle - Cooper, Dan; Reiness, Sean; Sidhu, Manika; Watson, Charlie (Physics Special Topics, 2017)
Miracles and other extraordinary events are often conceived as implausible in an age where fact challenges belief. In this article we calculate the power required to part the Red Sea and the force needed to sustain this miracle for the length of time necessary for the Israelites to cross: a feat Moses is believed to have accomplished in the Bible. Our calculated values for the power and force are 5.73 x 10^13 W and 8.63 x 10^12 N respectively.